Arthroscopic Ankle Fusion for Avascular Necrosis of the Talus. (May 2015) - Kendal, Adrian R.; Cooke, Paul; Sharp, Robert
Background: Avascular necrosis (AVN) of the talus is a painful condition leading to destruction of the ankle-hindfoot complex. Moderate outcomes and high complication rates are reported in small numbers of advanced disease treated with tibiotalocalcaneal fusion, which has the additional disadvantage of sacrificing both the ankle and subtalar joints. The blood supply of the talus is tenuous, and open procedures risk further talar collapse by disrupting extraosseous vessels. This article reports the outcome of arthroscopic ankle fusion for late-stage AVN of the talus. Our hypothesis was that arthroscopic ankle fusion would relieve symptoms of advanced talar AVN, prevent collapse of the talus, and preserve the subtalar joint. Methods: A cohort study was performed on 16 patients with talar AVN treated with arthroscopic ankle fusion. Our primary outcome was fusion rate. Secondary outcomes included perioperative complications, ongoing pain, and further operative intervention. All radiologic investigations were reported independently by a senior radiologist. The average age of the patients was 53.5 years. The presumed causes of talar AVN were steroids, trauma, hematologic disorders, and alcoholism. The etiology was unknown in 7 patients. One patient was lost to follow-up. Results: Clinical and radiologic fusion at the ankle joint was confirmed in 15 of 15 available patients. Thirteen patients reported resolution of pain at follow-up. Three patients had ongoing pain and underwent a subsequent successful subtalar fusion. Conclusions: Arthroscopic ankle fusion was a safe and reliable treatment of symptomatic advanced talar AVN. It was a minimally invasive procedure with minimal complication rate, preserving the talus and sparing the subtalar joint. Level of Evidence: Level IV, retrospective case series.